Research on the spatial differences and influencing factors of integrated urban-rural development in the Yangtze River Delta - Liu, Nina; Chen, Yingying; Su, Fei (Frontiers in Sustainable Cities, 2023)
Once the integrated urban-rural development enters a high-quality development stage, multiple dimensions would be reflected in population, space, economics, society, and environment, which will further advance sustainable development. An integrated urban and rural development have shown different features, rules, and models amid different social systems and in different development stages. Therefore, it's urgent to scientifically measure the integration level of rural and urban areas, revealing the spatial differences, characteristics, and internal mechanism. Targeting the 41 cities within the Yangtze River Delta, this paper evaluates the integrated urban-rural development in this area based on the global principal component analysis, explores its spatial agglomeration and evolution pattern by ESDA method, analyzes the principal factors that result in the spatial differences in integrated urban and rural development in the Yangtze River Delta and their interactive relations by the geographical detector, and discusses the regional differences between those influencing factors by the geographical weighted regression method. The results indicate that (1) the integrated development of the 41 cities is not balanced and there is a great difference between different cities. (2) The integrated development of this area has shown the apparent feature of geographical agglomeration, or in other words, the central cities have become the forces that drive the development of neighboring cities. (3) Since integrated urban-rural development is influenced by economic development, basic infrastructure, government support, and industrial structure, all regions should put forward suggestions for the formulation of policies accordingly based on realities.